Ang itim na kuting The black kitten - Viscarra, Natasha (Quezon City Adarna Book Services, 1996)
A story about the friendship between a girl and an "unlucky" cat..
Text in Filipino and English.
A book in 2 languages=cover
1996 Grand Prize Winner : PBBY Salanga Prize, PBBY Illustrator's Prize